2010
DOI: 10.1007/s00203-010-0552-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity against the fish pathogen Lactococcus garvieae produced by Lactococcus lactis TW34, a lactic acid bacterium isolated from the intestinal tract of a Patagonian fish

Abstract: After enrichment of Odontesthes platensis intestinal contents, 53 lactic acid bacteria (LAB) were isolated. From the four isolates that showed inhibitory activity against Lactococcus garvieae 03/8460, strain TW34 was selected because it exerted the strongest inhibition. It also inhibited other Gram-positive bacteria, but not Gram-negative fish pathogens. Phenotypic and 16S rDNA phylogenetic analyses showed that TW34 belongs to Lactococcus lactis. In addition, TW34 showed to be sensitive to different antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 47 publications
0
19
0
1
Order By: Relevance
“…Moreover, it has been observed that bacteriocins are able to inhibit other Gram positive bacteria genera including Bacillus and Staphylococcus. However, no inhibitory activity against Gram negative bacteria was found in these studies (Pinto et al, 2009;Rivas et al, 2012;Sequeiros, Vallejo, Marguet, & Olivera, 2010). It must be noted that CFS from E. mundtii Tw56 showed antibacterial activity against Ps.…”
Section: Detection Of Antimicrobial Activitymentioning
confidence: 82%
“…Moreover, it has been observed that bacteriocins are able to inhibit other Gram positive bacteria genera including Bacillus and Staphylococcus. However, no inhibitory activity against Gram negative bacteria was found in these studies (Pinto et al, 2009;Rivas et al, 2012;Sequeiros, Vallejo, Marguet, & Olivera, 2010). It must be noted that CFS from E. mundtii Tw56 showed antibacterial activity against Ps.…”
Section: Detection Of Antimicrobial Activitymentioning
confidence: 82%
“…; Desriac et al . ; Sequeiros, Vallejo, Marguet & Olivera ), short fatty acids (Vázquez et al . ), organic acids (Midolo, Lambert, Hull, Luo & Grayson ), hydrogen peroxide and carbon dioxide (Naidu, Bidlack & Clemenns ) that may act in synergy to inhibit or kill bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…mesenteroides CLFP 196, which produce antimicrobial substances against L. garvieae. Moreover, Sequeiros et al (2010) described the isolation of four LAB strains from the intestinal tract of Patagonian fish (Odontesthes platensis) with antimicrobial activity against L. garvieae, including the putative bacteriocinogenic strain L. lactis TW34. Regarding in vivo tests, the supplementation of fish feed with the probiotic putative bacteriocinogenic strains Lb.…”
Section: Discussionmentioning
confidence: 99%